In concern of the identity of the theory of education. Continuity and change in the multi-paradigmatic pedagogical research space. - Alina Wróbel (Studia z Teorii Wychowania)
The presented paper concerns the identity of the modern theory of education as the fundamental discipline of pedagogical (educational) sciences. The considerations refer to the theoretical development and research orientations used in the modern theory of education. In this context, the special focus was given to the importance of such analytical categories as theory, model, concept, and the theory-practice relationship of education.